PERSISTENCE AND ACCUMULATION OF ORGANOCHLORINE PESTICIDES IN SELECTED COCOA FARMS IN SOUTHWESTERN NIGERIA (2016)
Organochlorine Pesticides (OCPs) are cyclic chlorinated hydrocarbons that are toxic and can bioaccumulate in the environment. Although, its use has been prohibited in many countries including Nigeria; nevertheless they are still used extensively for pests control by cocoa (Theobroma cacao L.) farmers in Nigeria. In addition, OCPs residual concentrations among other factors in cocoa bean influences their price in the World market. Therefore, this study was designed to assess the persistence of OCPs in cocoa plants, soil, surface water, and sediments in selected cocoa farms in Southwestern Nigeria. The cocoa farms selected for this study were classified as; farms where OCPs have been used and discontinued for 15 years [Cocoa Research Institute of Nigeria, Ibadan [(CRIN (I&II)]; for 3–5 years (Sabo, Ondo); still in use [(Igba, Ondo) and (Sore-Bale, Ogun)]. Sampling was carried out during wet and dry seasons between November, 2009 and September, 2011. A total of 480 samples were randomly collected comprising: 120 soils [(0-15 and 15-30 cm), (CRIN I&II-48; Sore-Bale-24; Sabo-24; Igba-24)]; 60 surface water (CRIN I&II-24; Sore-Bale-12; Sabo-12; Igba-12); 60 sediments (CRIN I&II-24; Sore-Bale-12; Sabo-12; Igba-12); 60 each of leaves, bark, pods and seeds (CRIN I&II-24; Sore-Bale-12; Sabo-12; Igba-12, per matrix) for analysis. Control samples were collected 5.0 km from CRIN I, where OCPs were not used. Terrestrial Field Dissipation (TFD) and adsorption-desorption studies for OCP were done by EPA/OECD methods using endosulfan (6,7,8,9,10,10-Hexachloro-1,5,5a,6,9a-hexahydro-6,9-methano,2,4,3-benzodioxathiepin-3-oxide). Extractions and clean-up of OCPs were done using standard analytical methods. The OCPs were determined using Gas Chromatography-Mass Spectrophotometric (GC-MS) technique. Data were compared with WHO/FAO limits and analysed using correlation and descriptive statistics. Nineteen OCPs were detected in all the matrices. Total (∑) OCPs in vegetation (µgg-1), soil (ngg-1) ranged from <0.001 to 12.67 and 11.48 to 1,166.71, respectively. Amongst the Hexachlorocyclohexanes (HCHs), β-isomer was most predominant in CRIN. Bioaccumulation factors ranged from 0.1 to 658.0 in CRIN. The ∑OCP0-15cm < ∑OCP15-30cm except in Sore-Bale and Igba, due to fresh input. Total Endosulfan was the most dominant, while α-/β-endosulfan and endosulfan sulfate/endosulfan ratios in Sore-Bale were >1.7 (0-15 cm) and <0.3 (15-30 cm), respectively. Total OCPs residues in surface water ranged from 0.10-1.39 µgL-1 and 0.06-1.35 µgL-1 for dry and wet seasons, respectively. Igba and CRIN exceeded the WHO/FAO limit (1.0 µgL-1). The ∑OCPs in sediments ranged from 0.88 to 9.85 µgg-1, with γ-HCH (lindane) >0.01µgg-1; these values exceeded consensus-based threshold effect concentrations and probable effect concentrations. The TFD studies, showed initial ∑endosulfan distribution trend as; leaves > bark > pods > seeds. Dissipation half-life ranged from 7.93 to 79.82 days. Adsorption rate constants for endosulfan sorption studies ranged from 6.91 to 11.52×10-3 min-1 for CRIN, Sore-Bale and Igba soils. The Freundlich adsorption constants for non-linear isotherm curve (≤0.5574) supports the mechanism of adsorption. The presence of organochlorine pesticides in various matrices at Cocoa Research Institute of Nigeria and Sabo farms, established their persistence and accumulation. The pesticides were more adsorbed and persistent in the Cocoa Research Institute of Nigeria soil than other soils.